Literature review Cabai Jawa (Piper Retrofactum Vahl) dalam Proses Penyembuhan Luka - Prasetyo, Sigit Nian; Soesanto, Edy; Rejeki, Sri; Pranata, Satriya (Journal of Telenursing (JOTING), 2024)
This research aims to find out the extent of research that has been carried out and the results obtained regarding the use of Javanese chilies in the wound healing process. The method used in this research is to conduct a literature review. Literature search using Google Scholar, Science Direct and Pubmed databases from 2010 to 2023 with keywords in Indonesian: Javanese chili and wound healing process, and in English with keywords: piper retrofactum vahl, piper longum and wound healing process. Articles were selected using inclusion and exclusion criteria so that the results were 3 (three) articles in Indonesian that were in accordance with the research objectives. The conclusion of this research is that research on the influence of Javanese chilies in the wound healing process is still limited. Administration of Javanese chili extract can help in the wound healing process by increasing the number of macrophages, reducing leukocyte numbers and increasing the thickness of the epithelium in wounds. Keywords: Java chili, Wound healing, Literature Review